Environmental Reporting in Pakistan’s Oil and Gas Industry - Khan*(1), Muzammal; Hassan(2), Abeer (INTERNATIONAL RESEARCH JOURNAL OF BUSINESS STUDIES, 2019)
This paper investigates to what extent Oil and Gas (O&G) companies in Pakistan report on environmental protection activities. Using a content analysis approach, environmental reporting (ER) in 13 companies’ annual reports and websites are investigated over a five year period (2010-2014) following the guidelines issued by Securities Exchange Commission of Pakistan (SECP). Results reveal that the majority of the companies were found to have a low level of ER. However, since the introduction of SECP’s voluntary guidelines, the level of ER increased during the sample study period. Companies that issued a stand-alone report were found to have higher levels of disclosure on their environmental protection practices. This study recommends that management engages with internal and external stakeholders with their environmental management practices. The results may also be beneficial to the government as they provide reporting guidance and stock exchange regulations regarding the obligatory dissemination of environment-related information.Keywords: Environmental reporting, Oil & Gas Industry of Pakistan, Content Analysis(1,2) School of Business and Enterprise, University of the West of Scotland, United Kingdom* Corresponding Author https://doi.org/10.21632/irjbs.12.1.15-29